Efektifitas Pola Komunikasi Interpersonal antara Guru dan Siswa Autis dalam Pengembangan Kecerdasan Emosional : (Studi Kasus di SLB Putra Mandiri Rejotangan) - Ni’mah, Hamidatun; Harumike, Yefi Dyan Nofa; Basuki, Hery (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
This study aims to determine the effectiveness of interpersonal communication patterns between teachers and autistic students in developing emotional intelligence in SLB Putra Mandiri Rejotangan. The research method used is qualitative. Data collection techniques used were observation, interviews and documentation. The results of this study indicate that there is an effectiveness of communication patterns between teachers and autistic students in SLB Putra Mandiri Rejotangan, the application of communication by teachers and students is proven by the existence of openness, positivity, empathy, support, and similarity so that teachers are able to carry out their role as educators in a good manner. In carrying out the teaching and learning process at SLB Putra Mandiri Rejotangan it is hoped that teachers will continue to collaborate with parents in order to achieve maximum targets in learning and developing emotional intelligence.